Akyiğitzade Musa and conservation thought - Demir, Kenan (Turkish Entrepreneurship and Business Ethics Association, 2019)
In the 1830s, the idea of free trade entering the country through foreigners residing in the Ottoman Empire and having ambassadors of foreign consuls in Istanbul became an unrivaled system of thought until the 1880s. Firstly in the 1870s, the 1838 Trade Agreement was signed in light of the principle of free trade. In Tercuman-i Hakikat, Ahmet Mithat and Mizanci Murat demanded protective customs tariffs in Mizan for the country's economic development and protection of industry. Kazanli Akyigitzade Musa, who taught economics at the Military School in this period, also adopted the idea of patronage. In 1896, he said that the state should protect industry with customs walls for the economic development of Ottomans in his book Ilm-i Servet: Azadegi-i Ticaret and Usul-i Himaye. In this study, the authoritarian economic views of Akyigitzade Musa known as Iktisad yahud Ilm-i Servet: Azadegi-i Ticaret ve Usul-i Himaye ve Ilm-i Servet veyahut Ilm-i Iktisad will be given in the light of economics books.

Osmanlı Devleti’nde 1830’larda ülkede ikamet eden yabancılar ve İstanbul’daki yabancı konsoloslarındakielçiler vasıtasıyla ülkeye giren serbest ticaret düşüncesi 1880’lere kadar ülkede rakibi olmayan bir düşüncesistemi olmuştur. Öncelikle 1870’lilerde dönemin basınında serbest ticaret ilkesi ışığında imzalanan 1838ticaret anlaşmasının Osmanlı iktisadına verdiği zararlar anlatılmış ve 1880’lerde ise bu düşünceye karşıilk itiraz sesleri yükselmiştir. Tercüman-ı Hakikat’ta Ahmet Mithat ve Mizan’da Mizancı Murat ülkenin iktisadi açıdan kalkınması için koruyucu gümrük tarifeleri uygulanmasını ve sanayinin himaye edilmesiniistemişlerdir. Bu dönemde Harbiye Askeri Okulu’nda iktisat dersleri veren Kazanlı Akyiğitzade Musa dahimaye düşüncesini benimsemiş ve 1896 senesinde yazdığı İktisad yahud İlm-i Servet: Azadeği-i Ticaretve Usul-i Himaye adlı eserinde Osmanlı’nın iktisadi kalkınması için devletin sanayiyi gümrük duvarlarıile koruması gerektiğini ifade etmiştir. Bu çalışmada Akyiğitzade Musa’nın İktisad yahud İlm-i Servet:Azadeği-i Ticaret ve Usul-i Himaye ve İlm-i Servet veyahut İlm-i İktisad adlı kitapları ışığında himayeciiktisadi görüşleri değerlendirilecektir.
Akyiğitzade Musa ve himayecilik düşüncesi
Keywords: Ottoman Empire; Idea of Economic Suffering; Akyiğitzade Musa; Osmanlı Devleti; Himayeci İktisat Düşüncesi; Akyiğitzade Musa